(untitled) (Journal of Kidney Cancer, 2026)
We are pleased to present the abstracts accepted for the 2025 IKCS North America meeting! The research detailed here will be presented on stage and exhibited during our meeting, representing the best of what our scientific community has to offer. The ideas you will hear are both a review of what we understand so far about kidney cancer and an exciting look towards the future of how we can change the landscape for fellow researchers, practicing clinicians, and the patients and families who are relying on us to givethem hope as they face challenging diagnoses. Special thanks to our Scientific Planning Committee for their dedication in reviewing and selecting the research with the highest impact, the most creative ideas, and the most relevancy. I encourage you to engage with the science you hear as well as the people bringing these ideas forward! Together, we have the challenge and the privilege of shaping the future of kidney cancer.